Lithium iron phosphate dry-method electrode plate and preparation method thereof

Through dry film making technology, predispersion, fibrillation, granulation and hot rolling steps, high-load lithium iron phosphate dry electrode sheets were prepared, solving the problems of poor cracks, layering and flexibility of electrode sheets in wet coating technology, and achieving the improvement of battery energy density and cycle life.

CN119864369AActive Publication Date: 2025-04-22SHANDONG DONGYUE POLYMER MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510352160.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

When preparing high-load lithium iron phosphate electrode sheets by wet coating technology, there are problems of cracks, layering and poor flexibility, which limits the improvement of electrode thickness and energy density.

Method used

Using dry film making technology, high-load lithium iron phosphate dry electrode sheets are prepared through predispersion, fibrillation, granulation and hot rolling steps to ensure that the membrane remains intact and uniform under a thicker state.

Benefits of technology

The preparation of high-load lithium iron phosphate electrode sheets is achieved, the problems of uneven thickness and cracking of the diaphragm are solved, the mechanical properties and compaction density of the electrode are improved, the peel strength from the current collector is enhanced, and the energy density and cycle life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864369A_ABST
    Figure CN119864369A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery diaphragms, and particularly relates to a lithium iron phosphate dry-method electrode plate and a preparation method thereof. The electrode plate comprises a diaphragm and a current collector, wherein the diaphragm is prepared from the following components in percentage by mass: 90%-98% of lithium iron phosphate, 0.5%-5% of a conductive agent, 0.5%-4.9% of PTFE (Polytetrafluoroethylene) and 0.1%-1% of an adhesive polymer; the thickness of the membrane is 300 to 420 microns, the compaction density of the membrane is 2.6 to 3.2 g.cm <-3 >, and the peel strength of the membrane is 0.5 to 1.25 N.cm <-1 >. The high-load lithium iron phosphate dry-method electrode plate is obtained by improving the components of the diaphragm and the processing technology, the problems of nonuniformity and cracking when the thickness of the diaphragm is relatively large are solved, and the high-load lithium iron phosphate dry-method electrode plate has relatively high peel strength and battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery membranes, and in particular relates to a lithium iron phosphate dry-process electrode sheet and a preparation method thereof. Background Art

[0002] As a new generation of green high-energy batteries, lithium-ion batteries are widely used due to their high voltage, high energy density, good cycle performance, low self-discharge, no memory effect, and wide operating temperature range. Among them, safety, cost, and high energy density are the key to the large-scale application of lithium-ion batteries such as electric vehicles. Lithium iron phosphate (LiFePO4, abbreviated as LFP) has a stable PO bond and is difficult to decompose. Even under high temperature or overcharge conditions, the structure will not collapse. It has a stable operating voltage, is non-toxic and environmentally friendly, has a stable structure, good safety, good thermal stability, and an ultra-long cycle life, making it a hot material in the current research on lithium battery positive electrodes. However, its lower energy density compared to ternary positive electrode materials limits its development in the power battery market.

[0003] At present, there are many ways to improve the energy density of LFP batteries, such as reducing the proportion of inactive components, increasing the compaction density of electrode sheets, and increasing the thickness of electrode sheets. Among them, thick electrode sheets can greatly increase the load of active materials, thereby increasing the energy density of the battery. However, electrodes manufactured by wet coating technology have problems such as cracks, delamination, and poor flexibility, especially when thick electrodes are prepared. These problems will be magnified. Therefore, the thickness of the electrode is greatly limited by the wet coating technology. The dry film-making technology avoids the use of any solvents when preparing lithium battery electrode sheets, and can easily control the electrode thickness and the uniformity of thick electrodes, and has unique advantages in the preparation of thick electrodes.

[0004] Chinese patent document CN117352666A discloses a dry electrode pole piece and its preparation method and application, which introduces a coupling agent into the preparation process of dry electrode pole pieces for secondary batteries, reduces the amount of binder used, increases the proportion of conductive carbon content, optimizes some existing problems in the dry electrode preparation process, and greatly improves the peel strength of the pole piece while reducing the membrane resistance. However, this patent has problems of technical complexity and uneven material dispersion. The characteristic of dry electrode technology is that no solvent is added, but the addition of the coupling agent dispersion in the above patent causes solvents to appear in the electrode sheet preparation process. In addition, the viscosity of the coupling agent is very high, about 10 to 100 times that of water. It is difficult to disperse evenly by dry mixing and stirring when the coupling agent is directly added to the electrode material powder with a large specific surface area.

[0005] Chinese patent document CN112289976A discloses a positive electrode material layer, a preparation method thereof, a positive electrode sheet and a battery, comprising the following steps: 1) mixing a fiberizable polymer powder, a carbon-coated positive electrode active material and a conductive carbon material, and then drawing the fiberizable polymer powder into fibers under the action of shear force to obtain a mixture; 2) hot pressing the mixture on a current collector to a preset thickness to obtain the positive electrode material layer. The use of carbon-coated positive electrode active material improves the lubricity of the positive electrode material, improves the uniformity of the mixture, and effectively reduces the hardness of the positive electrode material, thereby improving the softness of the electrode sheet. The problem of uneven positive electrode material mixing and cracking of the electrode sheet caused by the large positive electrode material ratio and high hardness during the dry preparation of the positive electrode material layer is solved, and the requirements for the roller material of the roller press in the dry preparation of the positive electrode sheet can also be reduced, thereby reducing the equipment cost. However, the carbon coating content of the patent is between 2% and 15%, and when it exists in the positive electrode membrane, it will not provide any capacity, which will cause the problem of low mass and volume energy density. Summary of the invention

[0006] In order to solve the problems of cracks, delamination and poor flexibility of electrodes caused by using wet coating technology to prepare high-load LFP electrode sheets, the present invention provides a lithium iron phosphate dry electrode sheet and a preparation method thereof, which can ensure that the membrane remains intact and uniform in a relatively thick state.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a lithium iron phosphate dry-process electrode sheet, comprising a membrane and a current collector, wherein the membrane is composed of 90% to 98% by mass of lithium iron phosphate, 0.5% to 5% by mass of a conductive agent, 0.5% to 4.9% by mass of PTFE, and 0.1% to 1% by mass of an adhesive polymer; the membrane has a thickness of 300 to 420 μm and a compacted density of 2.6 to 3.2 g·cm -3 , peel strength is 0.5~1.25N·cm -1 .

[0008] The present invention also provides a method for preparing a lithium iron phosphate electrode sheet by a dry process, comprising the following steps: (1) Pre-dispersion: mixing lithium iron phosphate, conductive agent, PTFE and adhesive polymer at 10-19° C. to obtain a mixture; (2) Fibrillation: The mixed material is placed in a high-speed shearing machine for stirring, and the stirring termination temperature is controlled at 60-90°C to obtain a drawing agglomerate; (3) Granulation: The agglomerates after drawing are placed into a dry granulator and stirred to obtain granules with uniform particle size distribution; (4) Rolling: The pellets are rolled into a membrane of the required thickness through multi-stage rolling, and then the membrane is cut and rolled according to the size of the current collector; (5) Compounding: The rolled-up membrane and the current collector are rolled and compounded by a high-temperature roller press at the same speed to obtain a lithium iron phosphate dry-process electrode sheet.

[0009] Preferably, the conductive agent in step (1) is a mixture of one or more conductive agents selected from conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene, etc.; further preferably, the conductive agent is carbon black with a median particle size of 100-1000 nm and a specific surface area of ​​<100 m 2 / g.

[0010] Preferably, the particle size of the lithium iron phosphate in step (1) is 1 μm to 20 μm, and the specific surface area is 5 to 10 m 2 / g, tap density>0.8 g / cm 2 (GB / T5162), first discharge capacity>150mAh g -1 .

[0011] Preferably, in step (1), a high-speed mixer is used for mixing, a cooling medium is introduced into the jacket of the high-speed mixer, the stirring line speed is 15-25 m / s, and the stirring time is 3-5 minutes.

[0012] Preferably, the adhesive polymer in step (1) is one of ethylene-ethyl acrylate copolymer, ethylene acrylic acid copolymer, ethylene-methyl acrylate, ethylene methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, etc., or a mixture of two or more adhesive polymers thereof; further preferably, the adhesive polymer is ethylene-ethyl acrylate copolymer. The above-mentioned adhesive not only has strong adhesiveness, but also has certain flexibility and tensile strength. Compared with the electrode sheet using polyacrylate, the toughness and environmental stress cracking resistance of the electrode sheet using the above-mentioned adhesive are improved. Preferably, in step (2), the stirring speed of the high-speed shearing machine is 20-50 m / s, and the stirring is stopped when the temperature rises to 60-90°C, and the obtained wire drawing agglomerate is in the shape of "clay". It is further preferred that the stirring speed is 40-45 m / s, and the stirring end time is 65-90°C.

[0013] Preferably, in step (3), the line speed is set according to the particle size requirement. Further preferably, the line speed of the dry granulator is 3-4 m / s, the stirring time is 3-5 min, and the particle size D of the material after granulation is 50 1~2mm.

[0014] Preferably, in step (4), the roller gap and roller speed difference of each roller press are adjusted, and the roller temperature is raised to 100°C or above to maintain the good fiberization ability of PTFE. Further preferably, the roller press used is a three-stage roller press, and the gap between the first and second rollers is 1600~1000μm, preferably 1000-1200μm; the gap between the second and third rollers is 1000~500μm, preferably 500-800μm; the gap between the third and fourth rollers is 500~50μm, preferably 280-350μm. Preferably, the speed of the first roller is 10~18rpm / min, preferably 12-14 rpm / min; the speed ratio of each roller is 1~1.5, and the roller temperature is 100~200℃.

[0015] Preferably, in step (5), the linear speed of the isospeed roller can be adjusted according to the speed of the differential speed roller, and the roller speed of the isospeed high-temperature roller press is 10-40 rpm / min, preferably 18-24 rpm / min; the roller temperature is 100-200°C.

[0016] Preferably, the current collector in step (5) is one of battery-grade smooth aluminum foil, carbon-coated aluminum foil, perforated aluminum foil or glue-coated aluminum foil; further preferably, the current collector is smooth aluminum foil.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects or advantages: (1) The present invention obtains a high-load lithium iron phosphate dry-process electrode sheet by improving the membrane components and processing technology, thereby solving the problems of unevenness and cracking when the membrane thickness is relatively thick.

[0018] (2) The present invention uses high-speed blades to break up the conductive carbon, PTFE and adhesive polymer into a fluffy state, which is beneficial to improving the dispersibility of the conductive agent and making it less likely to agglomerate. The conductive agent with good dispersibility can provide higher conductivity. The mixture is blended at a low temperature and at a high speed to avoid inadequate mixing caused by fiberization of the adhesive during the mixing process.

[0019] (3) The present invention can realize continuous feeding through the three steps of fibrillation, granulation and hot rolling, and prepare a membrane with excellent mechanical properties and high compaction density.

[0020] (4) The present invention improves the peeling strength between the membrane and the current collector by optimizing the membrane components and adding an adhesive polymer. The adhesive polymer can increase the peeling force between the membrane and the aluminum foil after hot rolling, reduce the internal resistance of the lithium iron phosphate battery, and increase the battery cycle life. The use of this method to prepare dry electrode sheets is beneficial to improving the quality and performance of the battery and avoiding the problems of cracking and powder loss of thick membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the material after fibrillation treatment in Example 1 of the present invention; Figure 2 This is a first cycle charge and discharge curve diagram of the electrode sheet of Example 1 of the present invention; Figure 3 This is a performance diagram of the first 100 cycles of the electrode sheet of Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0023] It should be noted that the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and equipment described are all commercially available unless otherwise specified. Among them, PTFE is produced by Shandong Dongyue Polymer Materials Co., Ltd., with the brand name DF-213E. The lithium iron phosphate D 50 =1.1μm, specific surface area 0.9m 2 / g, tap density 0.87m 2 / g, first discharge specific capacity 155mAh / g; conductive carbon black D 50 =150nm, specific surface area 62m 2 / g; the mass content of ethyl acrylate in ethylene-ethyl acrylate copolymer is 22%.

[0024] Example 1 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was in a loose state and the bulk density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 40 m / s, and the stirring termination temperature is controlled at 65°C. The resulting second mixture is in the form of "clay"; (3) The second mixed material is granulated using a dry granulator at a granulator speed of 3 m / s for 3 min to obtain granulated material with a particle size of about 1.4 mm; (4) Rolling the film through a three-stage roller press to obtain a film sheet; adjusting the gap between the first and second rollers to 1200μm; the gap between the second and third rollers to 800μm; and the gap between the third and fourth rollers to 350μm. Set the speed of the first roller to 12rpm / min, the differential speed ratio of each roller to 1.2, and the roller temperature to 100℃. The obtained film sheet has no cracks on the surface and is 385μm thick, and can be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed at 18 rpm / min and the roller temperature at 150 °C to obtain the final electrode sheet.

[0025] from Figure 1The SEM image of the fibrillated material (the second mixture) shows that the PTFE becomes fibrillated after high-speed stirring, and a large number of fibers wrap around the material, which helps to improve the mechanical properties of the subsequent membrane calendering process.

[0026] The electrode sheet prepared in Example 1 was assembled into a CR2032 lithium half-cell for testing. The separator was a multilayer PE film, and the electrolyte was LiF6PO4 (concentration 1.1M) dissolved in a mixture of EC (ethylene carbonate) / DEC (diethyl carbonate) / DMC (dimethyl carbonate) with a volume ratio of 1:1:1. The amount of electrolyte used was generally 100 μL. The voltage test range was 2.25-3.75V, and the charge and discharge test was performed at a rate of 0.1C. From the electrochemical data of the electrode sheet ( Figure 2 and Figure 3 ) We found that the first-cycle charge / discharge specific capacity of the electrode sheet was 157.7 / 157.3 mAh / g, the initial capacity was as high as 99.7%, and the capacity was still 138.3 mAh / g after 100 cycles. The average capacity decay rate per cycle was only 0.12%, showing good electrochemical performance.

[0027] Example 2 (1) 4.5 kg of lithium iron phosphate, 0.25 kg of conductive carbon black, 0.245 kg of PTFE and 0.005 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 10° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 45 m / s, and the stirring termination temperature is controlled at 90°C. The resulting second mixture is in a "clay" state; (3) granulating the second mixed material at a granulator speed of 4 m / s for 3 min to obtain granules with a particle size of about 1.1 mm; (4) The film was calendered by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1000 μm; the gap between the second and third rollers was 500 μm; and the gap between the third and fourth rollers was 280 μm. The speed of the first roller was set to 12 rpm / min, the differential speed ratio of each roller was set to 1.2, and the roller temperature was set to 150 °C. The obtained film sheet had no cracks on the surface and a thickness of 324 μm, and could be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed being 18 rpm / min and the roller temperature being 200 °C to obtain the final electrode sheet.

[0028] Example 3 (1) 4.9 kg of lithium iron phosphate, 0.025 kg of conductive carbon black, 0.025 kg of PTFE and 0.05 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 19° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 45 m / s, and the stirring termination temperature is controlled at 90°C. The resulting second mixture is in a "clay" state; (3) granulating the second mixed material at a granulator speed of 4 m / s for 3 min to obtain granules with a particle size of about 1.1 mm; (4) The film was calendered by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1000 μm; the gap between the second and third rollers was 500 μm; and the gap between the third and fourth rollers was 280 μm. The speed of the first roller was set to 14 rpm / min, the differential speed ratio of each roller was set to 1.4, and the roller temperature was set to 200 °C. The obtained film sheet had no cracks on the surface and a thickness of 410 μm, and could be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed at 24 rpm / min and the roller temperature at 100 °C to obtain the final electrode sheet.

[0029] Example 4 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 45 m / s, and the stirring termination temperature is controlled at 90°C. The resulting second mixture is in a "clay" state; (3) granulating the second mixed material at a granulator speed of 4 m / s for 3 min to obtain granules with a particle size of about 1.1 mm; (4) The film was calendered by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1000 μm; the gap between the second and third rollers was 400 μm; and the gap between the third and fourth rollers was 280 μm. The speed of the first roller was set to 12 rpm / min, the differential speed ratio of each roller was set to 1.2, and the roller temperature was set to 100 °C. The obtained film sheet had no cracks on the surface and a thickness of 315 μm, and could be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed being 18 rpm / min and the roller temperature being 150 °C to obtain the final electrode sheet.

[0030] Example 5 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 45 m / s, and the stirring termination temperature is controlled at 90°C. The resulting second mixture is in a "clay" state; (3) granulating the second mixed material at a granulator speed of 4 m / s for 3 min to obtain granules with a particle size of about 1.1 mm; (4) The film was calendered by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1000 μm; the gap between the second and third rollers was 400 μm; and the gap between the third and fourth rollers was 280 μm. The speed of the first roller was set to 14 rpm / min, the differential speed ratio of each roller was set to 1.4, and the roller temperature was set to 100 °C. The obtained film sheet had no cracks on the surface and a thickness of 357 μm, and could be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed at 24 rpm / min and the roller temperature at 150 °C to obtain the final electrode sheet.

[0031] Comparative Example 1 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s for 3 min without temperature control to obtain a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 40 m / s and the stirring termination temperature is controlled at 65°C. The resulting second mixture is in the form of "clay"; (3) granulating the second mixed material at a granulator speed of 3 m / s for 3 min to obtain granules with a particle size of about 1.6 mm; (4) The film was calendered by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1200 μm; the gap between the second and third rollers was 800 μm; and the gap between the third and fourth rollers was 350 μm. The speed of the first roller was set to 12 rpm / min, the differential speed ratio of each roller was set to 1.2, and the roller temperature was 100 °C. The surface of the obtained film sheet had horizontal stripes and was discontinuous. The thickness was 607 μm and could not be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed at 18 rpm / min and the roller temperature at 150 °C to obtain the final electrode sheet.

[0032] Comparative Example 2 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 45 m / s, and the stirring termination temperature is controlled at 90°C. The resulting second mixture is in a "clay" state; (3) The "clay" second mixture was directly rolled into a film through a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1000 μm; the gap between the second and third rollers was 500 μm; and the gap between the third and fourth rollers was 280 μm. The speed of the first roller was set to 14 rpm / min, the differential speed ratio of each roller was set to 1.4, and the roller temperature was set to 100 °C. Because the fibrillated second mixture was too agglomerated, it could not be fed into a film.

[0033] Comparative Example 3 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, 0.08 kg of PTFE and 0.02 kg of ethylene-ethyl acrylate copolymer were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was in a loose state and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 40 m / s and the stirring termination temperature is controlled at 65°C. The resulting second mixture is in the form of "clay"; (3) The second mixed material is evenly spread on a metal plate with a smooth surface, and a stainless steel roller is used to manually roll the material into a film, which is then folded in half several times and rolled several times continuously until the film cannot be thinned any further. The obtained film is easily broken and has a thickness of 865 μm. (5) The obtained membrane was compounded with aluminum foil, with the roller speed being 18 rpm / min and the roller temperature being 150 °C to obtain the final electrode sheet.

[0034] Comparative Example 4 (1) 4.8 kg of lithium iron phosphate, 0.1 kg of conductive carbon black, and 0.1 kg of PTFE were placed in a high-speed blending device and stirred at a speed of 20 m / s and a temperature of 15° C. for 3 min until the mixture was loose and the volume density was measured to be a certain value, thereby obtaining a first mixed material; (2) The first mixture is stirred using a high-speed shearing machine at a linear speed of 40 m / s and the stirring termination temperature is controlled at 65°C. The resulting second mixture is in the form of "clay"; (3) granulating the second mixed material at a granulator speed of 3 m / s for 3 min to obtain granules with a particle size of about 1.4 mm; (4) The film was rolled into a film by a three-stage roller press to obtain a film sheet; the gap between the first and second rollers was adjusted to 1200 μm; the gap between the second and third rollers was 800 μm; and the gap between the third and fourth rollers was 350 μm. The speed of the first roller was set to 12 rpm / min, the differential speed ratio of each roller was set to 1.2, and the roller temperature was set to 100 °C. The obtained film sheet had fine cracks on the surface and a thickness of 399 μm, and could be rolled up; (5) The obtained membrane was compounded with aluminum foil, with the roller speed being 18 rpm / min and the roller temperature being 150 °C to obtain the final electrode sheet.

[0035] Test example The membranes obtained in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests, including membrane thickness, compaction density, and peel strength tests. The peel strength between the membrane and the aluminum foil was measured according to the ASTM D3330 standard; compaction density = membrane mass / membrane volume. The results are shown in Table 1.

[0036] Table 1. Performance data of the membranes obtained in Examples 1-5 and Comparative Examples 1-4

[0037] As can be seen from Table 1, the membrane prepared by the three steps of fibrillation, granulation and hot rolling shows excellent mechanical properties and high compaction density, and the peeling strength between the membrane and the aluminum foil is greatly enhanced after the addition of the adhesive polymer. The electrode sheet prepared by the method of the present invention can improve the energy density of the battery and reduce the cost of the battery, and has great commercial potential in the field of lithium iron phosphate batteries.

Claims

1. A lithium iron phosphate dry electrode sheet, characterized in that: The invention comprises a membrane and a current collector, wherein the membrane is composed of 90% to 98% by mass of lithium iron phosphate, 0.5% to 5% by mass of a conductive agent, 0.5% to 4.9% by mass of PTFE, and 0.1% to 1% by mass of an adhesive polymer; the membrane has a thickness of 300 to 420 μm and a compacted density of 2.6 to 3.2 g·cm -3 , peel strength is 0.5~1.25N·cm -1 .

2. The lithium iron phosphate dry electrode sheet according to claim 1, characterized in that: The conductive agent is a mixture of one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.

3. The lithium iron phosphate dry-process electrode sheet according to claim 1, characterized in that: The adhesive polymer is a mixture of one or more of ethylene-ethyl acrylate copolymer, ethylene acrylic acid copolymer, ethylene-methyl acrylate, ethylene methyl methacrylate copolymer, and ethylene-methacrylic acid copolymer.

4. The lithium iron phosphate dry-process electrode sheet according to claim 3, characterized in that: The adhesive polymer is ethylene-ethyl acrylate copolymer.

5. The method for preparing a lithium iron phosphate dry-process electrode sheet according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Pre-dispersion: mixing lithium iron phosphate, conductive agent, PTFE and adhesive polymer at 10-19° C. to obtain a mixture; (2) Fibrillation: The mixed material is placed in a high-speed shearing machine for stirring, and the stirring termination temperature is controlled at 60-90°C to obtain a drawing agglomerate; (3) Granulation: The agglomerates after drawing are placed into a dry granulator and stirred to obtain granules with uniform particle size distribution; (4) Rolling: The pellets are rolled into a membrane of the required thickness through multi-stage rolling, and then the membrane is cut and rolled according to the size of the current collector; (5) Compounding: The rolled membrane and the current collector are rolled and compounded by a high-temperature roller press at the same speed to obtain a lithium iron phosphate dry-process electrode sheet.

6. The preparation method according to claim 5, characterized in that: The mixing in step (1) has a stirring line speed of 15-25 m / s and a stirring time of 3-5 minutes.

7. The preparation method according to claim 5, characterized in that: The stirring linear velocity of step (2) is 20-50 m / s.

8. The preparation method according to claim 5, characterized in that: In step (3), the linear speed of the dry granulator is 3-4 m / s, and the stirring time is 3-5 min.

9. The preparation method according to claim 5, characterized in that: In step (4), the roller temperature is 100-200° C.; and the differential speed ratio of each roller of the multi-stage roller press is 1-1.

5.

10. The preparation method according to claim 5, characterized in that: In step (5), the roller speed of the high-temperature roller press is 10-40 rpm / min, and the roller temperature is 100-200°C.

Citation Information

Patent Citations

  • Lithium ion battery negative plate and preparation method thereof

    CN116053404A

  • Battery assembly and preparation method thereof, secondary battery and electrochemical device

    CN117673480A

  • Dry-method electrode binder, preparation method thereof and electrode slice

    CN119674075A

  • Negative electrode for lithium ion secondary battery, method for producing the same, lithium ion secondary battery and method for producing the same

    US20100009258A1

  • Binder for battery, composition for preparing electrode sheet, and use thereof

    WO2024199522A1